A new species of Habenaria (Orchidaceae, Asparagales) and a checklist of Orchidaceae from limestone outcrops of Brazil - Batista, João A.N.; Ferreira, Vera L.; Alves, Camila I.G.; Stehmann, João R. (European Journal of Taxonomy, 2022)
Habenaria karstica J.A.N.Bat. sp. nov., a new species from limestone outcrops (i.e., karst) in the State of Minas Gerais, Brazil, is described. The new species is ecologically very distinct since it is the only Neotropical species of the genus that grows on limestone outcrops under full sun, associated with mat-forming saxicolous plants. It is morphologically similar to species of the Habenaria repens complex, and separation is only possible through a combination of morphological characters. Bayesian and parsimony phylogenetic analyses based on nuclear (rDNA ITS, ETS) and plastid (matK-trnK, rps16-trnK) DNA markers revealed that H. karstica belongs to H. sect. Spathaceae. The new species, however, differs in floral morphology from the other species in this clade. A survey of the literature and public plants datasets revealed 122 species and 58 genera of Orchidaceae in karsts of Brazil. Although small compared to the family’s diversity in the country, Orchidaceae is among the families with the highest number of species in some karst localities. Our results indicate that approximately 97% of Orchidaceae found in karsts of Brazil is not limited to limestone outcrops areas, and that species composition of each locality is primarily determined by the regional flora and the biome in which it is located.